2009
DOI: 10.4103/0301-4738.57161
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of nasolacrimal duct obstruction: Dentigerous cyst in the maxillary sinus

Abstract: The most common abnormality of the lacrimal drainage system is congenital or acquired nasolacrimal duct obstruction. The causes of acquired nasolacrimal duct obstruction may be primary or secondary. The secondary acquired obstructions may result from infection, inflammation, neoplasm, trauma or mechanical causes. The maxillary sinus cysts usually obstruct the nasolacrimal duct mechanically. Dentigerous cysts are one of the main types of maxillary cysts. These cysts are benign odontogenic cysts which are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 5 publications
2
23
0
1
Order By: Relevance
“…This eruption may lead to local sinonasal sign and symptoms attributed to recurrent sinusitis. Obstruction the osteomeatal complex, formation of cyst in the maxillary sinus, obstruction of nasolacrimal canal leading to epiphora may occur because of the anatomic variation [3,4]. Approximately 50 cases of a tooth in the nasal cavity have been reported in the literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…This eruption may lead to local sinonasal sign and symptoms attributed to recurrent sinusitis. Obstruction the osteomeatal complex, formation of cyst in the maxillary sinus, obstruction of nasolacrimal canal leading to epiphora may occur because of the anatomic variation [3,4]. Approximately 50 cases of a tooth in the nasal cavity have been reported in the literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and proper interceptive intervention should be done to each child who is suspecting the presence of impacted supernumerary tooth or teeth (Figure 3 & 4) causing delayed eruption or impaction of 11 or 21 or other teeth. This will help to erupt the permanent tooth spontaneously into its place [10] or to reduce the chance of development of malocclusions or dentigerous cyst formation [3,4] or to prevent resorption of roots of adjacent teeth. On the other hand, if we delay the preventive and interceptive treatment to the impacted supernumerary tooth which had caused impaction of the permanent tooth ( Figure 2 & 3) may cause space loss in the dental arch (Figure 1) might require complex treatment plan later on.…”
Section: Discussionmentioning
confidence: 99%
“…It may cause mid-line diastema, rotation of incisors, crowding, ectopic eruption, impaction of incisor tooth or teeth, caries or periodontal disease. It may sometimes cause root resorption of adjacent tooth or even formation of a dentigerous cyst [3,4]. These supernumerary teeth may be impacted or erupted and sometimes they may erupt into the maxillary sinus or into the nasal cavity [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case was successfully managed surgically by Caldwell Luc approach. [7] Caldwell luc approach is recognized as a treatment for blow out fracture of orbit. Recently however studies have demonstrated minimally invasive techniques to manage blowout fracture.…”
Section: Discussionmentioning
confidence: 99%